Peringatan Dini Terhadap Hubungan Antar Umat Beragama di Kota Pangkalpinang - Rajab, Hadarah (Scientia: Jurnal Hasil Penelitian, 2018)
The harmony and conflict between religions of the institution becomes very important to: first, break down the prejudices against the image that has been built for the four institutions. The results of this study are expected to prove that the institution is truly inclusive. At the same time also reinforce the prejudice of the image, if it turns out the results of the study show the opposite. Second, it can be seen what their desires for religion and other groups treat them. In other words, this research is expected to be able to illustrate the desires of each religious group towards the other, so that in turn efforts can be made to build and increase harmony among them in particular, and among religious adherents in general. The research method used is Descriptive Phenomenology on How do community leaders view early warning of inter-religious relations in the City of Pangkalpinang and How are the efforts made, both by the government and the community, to increase harmony between religious adherents in the City of Pangkalpinang.?  Through social phenomena, it is known that based on the views of the Bangka community, it is known how much the potential for harmony and or conflict exists between them in particular, and in the Pangkalpinang City area in general. In other words, the results of this study contribute to the reading of the potential for conflict and or harmony between religions, each of which demands sustainable action and policy. Early warning in relations between religious communities is a form of anticipation of the possibility of religious conflicts. The term early warning or more commonly referred to as an early warning system, early warning system, is a term that is often used in a safety protection system, both those caused by natural disasters, or those caused by chaos that occur in society